Faktor Yang Memengaruhi Bank Syariah Di Indonesia Dalam Menyetujui Pembiayaan Pemilikan Rumah (PPR) Indent - Zikaillah Cinta Diramia; Irawan, Atika (PT Naureen Digital Education, 2023)
The Indent Home Ownership Financing (PPR Indent) is a financing product for the development of unfinished houses provided by Islamic banks to housing developers and financing customers. Due to the lack of research that can assist housing developers in creating optimal portfolios and housing development projects to facilitate the approval of Indent Home Ownership Financing (PPR Indent) financing, this study aims to identify the factors influencing Indonesian Islamic banks in approving such financing and how these factors affect the decision-making process. The study employed an Exploratory-Descriptive Qualitative (EDQ) approach, using interview methods with one Islamic Commercial Bank (BUS) and one Islamic Business Unit (UUS) through purposive sampling, with data analysis conducted using Interpretative Data Analysis. The research findings reveal that Islamic banks in Indonesia approve PPR Indent financing by considering the probability of Non-Performing Financing (NPF) risks, thus implementing Prudential Banking Principles. This is done through the analysis of the 5C (Character, Capacity, Capital, Collateral, and Condition of Economic) of financing customers and the ability, experience, and willingness of housing developers to bear moral hazard through buyback agreements. Each Islamic bank in Indonesia has different prioritization processes and decision-making processes for these factors.